Oral streptococci: modulators of health and disease - Bloch, Susanne; Hager-Mair, Fiona F.; Andrukhov, Oleh; Schäffer, Christina (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococci are primary colonizers of the oral cavity where they are ubiquitously present and an integral part of the commensal oral biofilm microflora. The role oral streptococci play in the interaction with the host is ambivalent. On the one hand, they function as gatekeepers of homeostasis and are a prerequisite for the maintenance of oral health -they shape the oral microbiota, modulate the immune system to enable bacterial survival, and antagonize pathogenic species. On the other hand, also recognized pathogens, such as oral Streptococcus mutans and Streptococcus sobrinus, which trigger the onset of dental caries belong to the genus Streptococcus. In the context of periodontitis, oral streptococci as excellent initial biofilm formers have an accessory function, enabling late biofilm colonizers to inhabit gingival pockets and cause disease. The pathogenic potential of oral streptococci fully unfolds when their dissemination into the bloodstream occurs; streptococcal infection can cause extra-oral diseases, such as infective endocarditis and hemorrhagic stroke. In this review, the taxonomic diversity of oral streptococci, their role and prevalence in the oral cavity and their contribution to oral health and disease will be discussed, focusing on the virulence factors these species employ for interactions at the host interface.